Genetic variability of the Mite Varroa destructor Isolated from Honey Bees in Iraq and Some Middle Eastern Countries - Muntasser S. Mahdi1 , Mahmood B. Ali 1, Aqeel N. AL-abedy2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study was conducted to isolate and diagnose different isolates of Varroa parasite collected from different regions of Iraq, Iran, Turkey, Syria, Egypt, and Jordan. The different Varroa isolates were identified using the polymerase chain reaction (PCR) technique to amplify the mitochondrial cytochrome oxidase gene I (mtCOI) to determine the nucleotide sequences generated from these isolates. These nucleotide sequences were analyzed to identify the similarities and differences in the amplified gene regions. The results obtained from the nucleotide base-sequence analysis indicated that all isolates of Varroa parasite collected in this study were Varroa destructor. Furthermore, the results showed differences in the nucleotide sequences resulting from the amplification of the target mtCOI by PCR. The isolates from Egypt (No.12) and from Syria (No.14) were the most genetically different among the other isolates in this study (17 samples) . By the phylogenetic tree analysis, isolates of parasites numbered with 12 and 14 appeared in separate clades from the other clades of isolates under study. Besides, these isolates (No.12 and No.14) showed differences to other isolates of the same parasite formerly recorded at NCBI. The V. destructor isolate of Egypt (12) and Syria (No.14) showed a genetic similarity of 99%.